An anodic aromatic C, C cross-coupling reaction using parallel laminar flow mode in a flow microreactor. Issue 23 (23rd February 2015) - Arai, Toshihiro; Tateno, Hiroyuki; Nakabayashi, Koji; Kashiwagi, Tsuneo; Atobe, Mahito
Abstract : An efficient anodic aromatic C, C cross-coupling reaction was successfully demonstrated by using parallel laminar flow mode in a two-inlet flow microreactor. Abstract : We have successfully demonstrated an efficient anodic aromatic C, C cross-coupling reaction using parallel laminar flow mode in a two-inlet flow microreactor. The model reaction proceeded effectively even in single flow-through operations and the desired cross-coupling product was obtained in much higher current yields compared to the reaction in a conventional batch type cell.